Pengolahan Limbah Kulit Kopi sebagai Pupuk Organik Tanaman Kopi di Desa Tapak Gedung Kabupaten Kepahiang - Sura Menda Ginting; Dewi Handayani; Mimi Sutrawati (Universitas Bengkulu, 2022)
Community service was conducted in Tapak Gedung Village, Kepahiang Regency to coffee farmers. This activity aims to enrich to coffee farmers and gives training on processing coffee bean waste (coffee bean skins) into liquid organic fertilizer with green chemistry principle. The material of how fertilizer processing was given by a lecturer from Agriculture Faculty continued by practical training on how the liquid organic fertilizer was made from coffee bean waste. This activity was followed by around 30 participants with high enthusiasm on the training. The production of organic fertilizer was done by mixing local microorganism, coffee bean waste and water into an airtight container. The result was brownish liquid with distinct alcohol odor, which indicates decomposition process by microorganism. Evaluation pre-activity using questionnaire showed that most respondents had little to no knowledge of how to utilize coffee bean waste, and post-activity questionnaire result showed that more than 90% respondents agree to utilize liquid organic fertilizer as replacement for synthetic fertilizer and agree to sustainably continuing the program to utilize coffee bean waste as liquid organic fertilizer.